(untitled) (Global Journal of Medical Research, 2016)
Cerebral vasospasm (CVS) is a common and severe complication of aneurysmal subarachnoid hemorrhage (aSAH). Despite the improvement in treatment of aSAH, CVS complicating aSAH has remained the main cause of death. CVS begins most often on the third day after the ictal event and reaches the maximum on the 5th-7th postictal days. Several therapeutic modalities have been employed to prevent or reverse CVS. The aim of this review is to emphatically introduce some kind of pharmacological agent for vasospasm.